DNA-based molecular lithography for nanoscale fabrication. - Brenan, C.J.H (IEEE Engineering in medicine and biology magazine)
Taking a cue from nature, self-assembly of molecular building blocks to form larger-scale functional elements is an attractive, "bottoms-up" approach for fabricating nanometer-size devices. DNA is a promising construction material for growing well-defined nanostructures. DNA oligonucleotides have unique and predictable recognition capabilities and materials of different properties (e.g., proteins) can be readily synthesized from this template. Furthermore, nucleic acids can be processed with exquisite precision by enzymes such as nucleases and polymerases.